Methods an assessment of economic safety of the production sphereof the integrated production structure (Путеводитель предпринимателя, 2020)
The perspective of tasks’ development and statement, methods and models of assessment and ensuring economic safety of manufacturing enterprise, as a part of which the independent business units, differing with the risk size of the production sphere is considered.